Analisis pengaruh dana perimbangan dan investasi terhadap pertumbuhan ekonomi di Kabupaten/Kota dalam Provinsi Jambi - Moh Sahroni Nurkodri; Amir, Amri; Zamzami, Zamzami (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2023)
The purpose of this research is to examine the impact of equalization funds and investment on economic growth in a Jambi Province regency or municipality. Time series data from 2010 to 2021 were used, as well as cross-section data from 11 regencies or municipalities in Jambi Province. The data is sourced from the BPS Regency of Jambi Province, the Directorate General of Fiscal Balance of the Ministry of Finance of the Republic of Indonesia, and the Ministry of Investment/BKPM. Panel regression analysis was used to examine the data. The findings show that partially general allocation fund, sharing revenue and investment have a significant impact on economic growth. In this analysis, the special allocation funds variable has no significant impact on economic growth in the region or municipality of Jambi Province. This study's dependent variables are all significant to economic growth in the region or municipality of Jambi Province